The Effectiveness of TV Rehabilitation as a Component of a Comprehensive Home Rehabilitation Program for Patients Diagnosed with Coronary Heart Disease (Angina Pectoris, Functional Class I) and Obesity of the First Degree - N. Makarchuk; T. Bakaliuk; H. Stelmakh; L. Martynyuk (Львівський клінічний вісник)
Introduction. Coronary heart disease (CHD) is one of the leading causes of disability and mortality. Telerehabilitation as an innovative approach provides remote monitoring and personalized support, increasing the accessibility and effectiveness of rehabilitation.